Culinary Medicine as Innovative Nutrition Education for Medical Students: A Scoping Review. (2nd August 2022) - Newman, Courtney; Yan, Justin; Messiah, Sarah E.; Albin, Jaclyn
Abstract : Purpose: Lifestyle-related disease substantially impacts health, but physicians lack adequate nutrition education to discuss behavioral change with patients. Many medical schools have developed culinary medicine programs as a nutrition education strategy, but common elements of success have not been defined. Method: The authors conducted a scoping review of the literature on culinary medicine programs for medical students. They searched PubMed, Ovid MEDLINE, and MedEdPORTAL databases to identify English-language studies published between January 1, 2012, and October 15, 2021. Multiple search terms were used to identify medical student–focused culinary medicine programs. The authors focused inclusion criteria on medical student learners, curricular description, hands-on cooking components, reflection or application to patient care, and assessment. Additionally, the authors reviewed 2 online databases which list programs delivering culinary medicine education for U.S. medical students. Results: Authors identified 251 studies, of which 12 met inclusion criteria. These studies described programs that used a kitchen or similar space adaptable for food preparation to enable hands-on learning, and some programs provided opportunities for practical application. Most programs administered surveys to assess course impact, but the type of survey and cohort size varied. Culinary medicine programs for medical students varied in learner level, number of participants, course length and structure, and instructor background but consistently improved student knowledge in key areas of nutrition application and changed knowledge and attitudes about food and nutrition. Funding was often noted as a barrier to program sustainability. When funding source was provided, it derived from philanthropic or academic sources. When the authors reviewed the 2 online databases, they identified 34 programs offering medical student-focused culinary medicine courses. Conclusions: As culinary education programs emerge across academic centers, standardizing programmatic and curricular elements, best practices, and assessment strategies will be vital for quality control, sustainability, and optimal population health impact.